Artificial Intelligence in Education: Opportunities, Risks, and Pedagogical Implications for Higher Education - Agung Yuliyanto Nugroho; Marnangkok Pakpahan; Yessy Ade Winarti; Nurul Hikmah (PT. Sinergi Bersahaja Sejahtera, 2025)
Background: The rapid integration of Artificial Intelligence (AI) in various sectors, including education, is transforming the way teaching and learning processes are conducted. AI has the potential to revolutionize higher education by enhancing learning experiences, improving teaching efficiency, and providing personalized learning opportunities. However, the use of AI in education also brings with it potential risks, such as data privacy concerns, reliance on automated systems, and the impact on traditional pedagogical methods. Purpose: This study explores the opportunities, risks, and pedagogical implications of integrating Artificial Intelligence in higher education. Specifically, it examines how AI tools can be utilized to enhance teaching, the challenges they present, and the ways in which educators and institutions can adapt to these technological changes to maximize their benefits. Method: A qualitative approach was used to analyze relevant literature, case studies, and expert opinions on the use of AI in education. Interviews with higher education faculty and technology experts were conducted to gain insights into the practical applications and challenges of AI integration. Results: The findings highlight that AI offers significant opportunities for personalized learning, data-driven decision-making, and administrative efficiency. However, it also poses risks related to data privacy, ethical concerns, and the potential for exacerbating educational inequalities. The pedagogical implications suggest a need for educators to develop new competencies and adapt teaching strategies to effectively integrate AI into the curriculum. Conclusion: The integration of AI in higher education presents both significant opportunities and challenges. To fully harness the potential of AI while mitigating its risks, higher education institutions must prioritize ethical considerations, data privacy, and the development of pedagogical strategies that complement AI technologies.